Pentingnya Literasi Keuangan Bagi Pengelolaan Keuangan Pribadi - Anindia Dwitri; Sugeng Pradikto (Institut Nalanda, 2025)
Financial literacy is an essential skill that enables people to handle their personal money responsibly. With good financial literacy, people can make sound financial decisions, identify problems with debt, and manage their time effectively. This also contributes to lowering the risk of financial failure and improving economic stability. Financial literacy education should start as soon as possible so that future generations can overcome economic challenges and achieve financial stability.